2017
DOI: 10.1111/jdv.14456
|View full text |Cite
|
Sign up to set email alerts
|

Association of atopy and tentative diagnosis of skin cancer – results from occupational skin cancer screenings

Abstract: Design limitations of the study include that all findings of skin cancer were based on clinical examination only and must therefore be considered tentative diagnoses. Furthermore, owing to the cross-sectional study design, causal pathways cannot be proven. However, analyses of data from such a large and general population-based cohort afford valuable insights into the relationship between atopic diseases and skin cancer. They provide the grounds for prospective cohort studies to evaluate and dissect the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 23 publications
1
21
0
4
Order By: Relevance
“…This assessment was applied as the overall clinical impression of all body sites. Atopic disposition was defined as discussed previously as pre‐existing conditions of pollen, house dust mite or animal hair allergy or atopic eczema …”
Section: Methodsmentioning
confidence: 99%
“…This assessment was applied as the overall clinical impression of all body sites. Atopic disposition was defined as discussed previously as pre‐existing conditions of pollen, house dust mite or animal hair allergy or atopic eczema …”
Section: Methodsmentioning
confidence: 99%
“…20 publications on the prevalence of MM were included, both registry studies and primary data compilations [10-17, 19, 21, 24-29, 31, 32, 34, 35]. Prevalence rates of MM were analyzed in several studies and showed varying sex-specific differences (Table 3) [11][12][13]27]. Augustin et al also reported higher one-year prevalences in urban regions as compared with rural areas.…”
Section: Malignant Melanomamentioning
confidence: 99%
“…Eleven publications on the epidemiology of NMSC were included [9, 11-14, 16, 20, 22, 26, 28, 29]. The sex-specific prevalences for NMSC as well as for basal cell carcinoma (BCC) showed a preponderance of male patients (Table 3) [11][12][13]. Incidence rates of squamous cell carcinoma (SCC) were generally lower than those of BCC [26,28,29].…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…Another possible confounding factor not addressed in the study of Thyssen et al (2018) is the presence of AD, which is more prevalent in the carriers of FLG mutations. In a recent cross-sectional study of Sch€ afer et al, 5 atopic diseases showed significantly protective against MM. Clearly, there are several pathways by which filaggrin may modify the risk for MM; however, the overall effect of FLG mutations is difficult to assess.…”
mentioning
confidence: 90%